2006
DOI: 10.1021/ef0601869
|View full text |Cite
|
Sign up to set email alerts
|

Control Mechanisms for Gas Hydrate Production by Depressurization in Different Scale Hydrate Reservoirs

Abstract: The methane hydrate was formed in a pressure vessel 38 mm in id and 500 mm in length. Experimental works on gas production from the hydrate-bearing core by depressurization to 0.1, 0.93, and 1.93 MPa have been carried out. The hydrate reservoir simulator TOUGH-Fx/Hydrate was used to simulate the experimental gas production behavior, and the intrinsic hydration dissociation constant (K 0 ) fitted for the experimental data was on the order of 10 4 mol m -2 Pa -1 s -1 , which was one order lower than that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
123
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(127 citation statements)
references
References 11 publications
3
123
0
1
Order By: Relevance
“…The results indicate that 36% of CH 4 in small cages was replaced with k 1 of 0.0007 min −1 , while 31% of CH 4 in large cages was replaced during 17 h with k 1 of 0.0002 min −1 (Figure 2). This is in a good agreement with 1 H NMR data as the amount of replaced methane is 25% during 17 h. As the large cages outnumber the small cages by a factor of 3 in structure I hydrate, the amount of replaced CH 4 should be much larger in large cages than small cages. Figure 3(a),(b) shows the amount of methane in large and small cages, respectively, which was obtained from the integrated intensities in Figure 2 and the unit cell composition of structure I methane hydrate.…”
Section: ■ Experimental Sectionsupporting
confidence: 86%
See 4 more Smart Citations
“…The results indicate that 36% of CH 4 in small cages was replaced with k 1 of 0.0007 min −1 , while 31% of CH 4 in large cages was replaced during 17 h with k 1 of 0.0002 min −1 (Figure 2). This is in a good agreement with 1 H NMR data as the amount of replaced methane is 25% during 17 h. As the large cages outnumber the small cages by a factor of 3 in structure I hydrate, the amount of replaced CH 4 should be much larger in large cages than small cages. Figure 3(a),(b) shows the amount of methane in large and small cages, respectively, which was obtained from the integrated intensities in Figure 2 and the unit cell composition of structure I methane hydrate.…”
Section: ■ Experimental Sectionsupporting
confidence: 86%
“…This phenomenon implies that the CH 4 is replaced steadily by the gas mixture of 20 mol % CO 2 , balance N 2 . The change in CH 4 peak intensity was monitored in order to identify the amount of CH 4 recovered from hydrate cages. When the experiment ran for 65 h, it was confirmed that 42 mol % of CH 4 was replaced.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations